Simulation and optimization of fluid catalytic cracking processes for environmentally friendly light products - Moyo, Nomzamo Qaziwe (My University, 2018)
The rapid industrialization that happened in the early turn of the 18th century came with a lot of positives, and these include the invention of engines which became the back bone of a number of industrial equipment. In the 20th century the draw backs of the continuous industrialization came to light, the hole in the ozone layer was discovered, this led to industrialists being urged to try and find better ways to achieve production whilst decreasing their carbon foot print. Refinery emissions contributed greatly to the carbon foot print, and it is worth investigating ways to reduce the amount of emissions. The Fluid Catalytic Cracking (FCC) unit, which is the heart of most refineries, is one such unit that contributes up to 10% of a refinery’s greenhouse emissions. Due to the high emissions from the FCC unit a number of studies are being conducted to try and curb the high emissions. This project is aimed at finding ways to reduce the amount of CO2 that is emitted into the atmosphere as well as to optimize on the energy used. A simulation in Aspen HYSYS was built and a case study was performed to help find the optimum operating point of the FCC. A discussion of the results has been conducted and recommendations given.
Submitted to School of Chemical and Metallurgical Engineering, Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, South Africa December 2018